2(x - 5)^2 = 3
So (x - 5)^2 = 3/2
Thus x - 5 = ± √(3/2)
= ± √6 / 4
Thus x = 5 ± √6 / 4
2006-11-10 12:10:24
·
answer #1
·
answered by Wal C 6
·
0⤊
3⤋
Foil out the (x-5)^2:
2(x^2-10x+25)=3
Distributive property:
2x^2-20x+50=3
Subtract 3 on both side to set it to zero:
2x^2-20x+47=0
You want to use the quadratic formula:
x=-b±√b^2-4ac/2a
20±√(20)^2-4(2*47)/2(2)
20±√400-4(94)/4
20±√(400-376)/4
(20±2√6)/4
2006-11-10 12:35:03
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
since you have ^2 this means you have 2 (x-5)
it will look like this
2(x-5)(x-5) =3
you would do this step called foil
F-first
o- outer
i- inner
l - last
2x + 2x - 10 + 25 = 3
combine like terms
4x + 15 =3
subtract the 15 over to the 3 side
4x = -12
divide the 4 over
x = -3
I think this is correct it has been a loooong time since i did math
2006-11-10 12:18:24
·
answer #3
·
answered by The cuter 3
·
0⤊
2⤋
2(x - 5) ^ 2 = 3
2(x^2 - 10x + 25) = 3
2x^2 - 20x + 50 = 3
2x^2 - 20x + 47 = 0
Now use the quadratic formula by following this format (ax^2 + bx + c)
( - b + (or - ) sq rt(b^2 - 4ac)) / 2a
(20 + (or - ) sq rt(400 - 376)) / 4 = (20 + (or - ) sq rt (24))/4
(20 + (or - ) 2 * sq rt (6))/4
round answers
x = 6.225
x = 3.775
2006-11-10 12:15:03
·
answer #4
·
answered by trackstarr59 3
·
1⤊
0⤋
2(x^2 - 10 x + 25)=3
2x^2 - 20 x + 47 = 0
then use quadriatic formula
2006-11-10 12:21:10
·
answer #5
·
answered by scurvybc 3
·
1⤊
0⤋
2(x - 5)² = 3
(2x - 10)² = 3
2x - 10 = ± √3
2x - 10 + 10 = 10 ± √3
2x / 2 = 10/2 ± √3/2
x = 5 ± √3/2
- - - - - -s-
2006-11-10 23:22:46
·
answer #6
·
answered by SAMUEL D 7
·
0⤊
0⤋
all you need to do is "undo" the operations:
step 1: divide bothe sides by 2
step 2: obtain the square root of both sides
step 3: add 5 to both sides
step 4: if needed, rationalize the result.
in all, x = sqrt(3/2) + 5
after rationalization:
x = [sqrt(6) + sqrt(10)]/2
2006-11-10 12:17:42
·
answer #7
·
answered by naglibog 2
·
1⤊
0⤋
foil
2(x-5)(x-5)=3
2(x^2-10x+25)=3
parenthesis
2x^2-20x+50=3
subtract 3 on both sides
2x^2-20x+47=0
use the quadratic formula, and you can figure out the rest
2006-11-10 12:12:05
·
answer #8
·
answered by aznfobboytly 3
·
1⤊
1⤋
you have one answer from this question already right which is -2 so if you do synthetic division you will eventually get (x+2)(x^2+1) = 0 So there fore the other two answers are x = +/- i, in which " i " is an imaginary number Maths rock :)
2016-05-22 03:58:14
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
2(x^2-10x+25)=3
2x^2-20x+50=3
2x^2-20x+47=0
x=[20 +/- sq.root (400-4(2)(47)] / 4
x=[20 +/- 2 sq.root 6]/4
x=[10 +/- sq.root 6]/2
2006-11-10 15:08:45
·
answer #10
·
answered by abcde12345 4
·
1⤊
1⤋